Gesture bike: examining projection surfaces and turn signal systems for urban cycling - Dancu, Alexandru; Vechev, Velko; Unluer, Adviye Ayca; Nilson, Simon; Nygren, Oscar; Eliasson, Simon; Barjonet, Jean-Elie; Marshall, Joe; Fjeld, Morten (2015)
Interactive surfaces could be employed in urban environments to make people more aware of moving vehicles, showing drivers’ intention and the subsequent position of vehicles. To explore the usage of projections while cycling, we created a system that displays a map for navigation and signals cyclist intention. The first experiment compared the task of map navigation on a display projected on a road surface in front of the bicycle with a head-up-display (HUD) consisting of a projection on a windshield. The HUD system was considered safer and easier to use. In our second experiment, we used projected surfaces to implement concepts inspired by Gibson’s perception theory of driving that were combined with detection of conventional cycling gestures to signal and visualize turning intention. The comparison of our system with an off-the-shelf turn signal system showed that gesture input was easier to use. A web-based follow-up study based on the recording of the two signalling systems from the perspective of participants in traffic showed that with the gesture-projector system it was easier to understand and predict the cyclist intention.